Simulation of Neutrons Shielding Properties for Some Medical Materials - WAHEED, Faez; İMAMOĞLU, Meltem and KARPUZ, Nurdan and OVALIOĞLU, Hüseyin (International Journal of Computational and Experimental Science and Engineering, 2021)
Radiation is used different field and among others neutron is the one of the most hazardous particle as it is neutral and heavy. Its neutral characteristics make it more difficult particle to be shielded. In this study neutron shielding properties for some medical interested materials of water, fat and bone have been obtained using Phy-X/PSD software.